Roles of preoperative C-reactive protein are more relevant in buccal cancer than other subsites. Issue 1 (December 2017) - Tai, Shiao; Chien, Huei-Tzu; Young, Chi-Kuang; Tsao, Chung-Kang; de Pablo, Alba; Fan, Kang-Hsing; Liao, Chun-Ta; Wang, Hung-Ming; Kang, Chung-Jan; Chang, Joseph; Huang, Shiang-Fu
Abstract Background C-reactive protein (CRP) is an early marker for inflammation, and a relationship between serum CRP levels and survival in oral cancer has been demonstrated previously. In this study, we investigated the roles of CRP in different oral cancer subsites. Methods Three hundred and forty-three oral squamous cell carcinoma patients between June 1999 and March 2015 were retrospectively reviewed. Serum CRP levels were measured preoperatively. Results The elevation of CRP levels (≥5.0 mg/L) was significantly correlated with pathologic tumor status, pathologic nodal status, nodal extracapsular spread, tumor stage, skin invasion, tumor depth (≥10 mm), and bone invasion. The correlation between elevation of CRP and clinicopathologic factors was more evident in the buccal cancer compared to other tumor subsites. The disease-free survival and overall survival correlation was significant in buccal cancer (p  = 0.003 andp  < 0.001) but not in tongue cancer (p  = 0.119 andp  = 0.341) or other oral cancer subsites (p  = 0.246 andp  = 0.696). Conclusions Preoperative serum CRP level was a prognosticator in oral squamous cell carcinoma, and its effect was more prominent in buccal cancer that occurs more frequently in areca-quid (AQ) endemic regions.